Does two-dimensional vs. three-dimensional surgical simulation produce better surgical outcomes among patients with class III facial asymmetry?. Issue 8 (August 2018) - Udomlarptham, N.; Lin, C.-H.; Wang, Y.-C.; Ko, E.W.-C.
Abstract: The aim of this study was to compare the outcomes of traditional two-dimensional planning (2DP) and three-dimensional surgical simulation (3DS) in the surgical correction of skeletal class III with facial asymmetry. This retrospective cohort study included 37 consecutive adult Taiwanese patients. Preoperative and postoperative three-dimensional cephalometric measurements were obtained from cone beam computed tomography scans. The outcome variables were the differences in preoperative and postoperative linear and angular measurements and the differences between the two groups after surgery. When the surgical result was compared between the 2DP and 3DS groups, significant differences were found for four cephalometric variables: the distance from gonion on the non-deviated side to the midsagittal plane (MSP), mid-gonion to the MSP, upper first molar on the non-deviated side to the Frankfort horizontal plane, and the yaw angle. In the 3DS group, mandibular symmetry was achieved because the centre between the bilateral gonions was improved, and because there was no significant difference in the horizontal gonion (Go to the MSP) between the deviated and non-deviated sides after surgery. 3DS provides all the necessary information for planned surgical movements for the correction of facial asymmetry; it should be considered during surgical planning to improve surgical outcomes, particularly the achievement of bilateral mandibular contour symmetry.